Characterizations of saponin and phenolic bioactive compounds extracted from fenugreek seed and aloe vera leaves via microwave-assisted extraction method - Sweeta, Akbari (2021)
In this study, the potential of fenugreek seed and Aloe vera leaves as a source of saponins, phenolics and antioxidants were investigated. Microwave-assisted extraction (MAE) and Soxhlet extraction (SE) were used to obtain the extracts. The effects of experimental factors in MAE such as extraction time (2-12 min), microwave power (300-700 W), ethanol concentration (20-100%), feed-to-solvent ratio (1:8-1:16 and 1:18-1:22 g/mL) and extraction temperature (40-80 °C) were evaluated using one-factor-at-a-time (OFAT), respectively. The SE factors including extraction time (1-5 h), ethanol concentration (20-100%) and feed-to-solvent ratio (1:14-1:24 g/mL) were also investigated. Results indicated the higher extraction yield, total saponin content (TSC) and Total phenolic content (TPC) were obtained via MAE compared to SE in a time saving process. The maximum yields in SE were obtained at 3 h of extraction time, 60 % ethanol concentration and 1:20 g/mL F:S ratio which were 19.35±0.75%, 125.04±1.55 mg DE/g d.w. and 60.13±2.04 mg GAE/g d.w. for fenugreek seed and 22.45±0.76%, 44.78±1.01 mg OAE/g d.w. and 49.99±0.56 mg GAE/g d.w. for Aloe vera leaves, respectively. Further screening of the factors via two-level factorial design was carried out for MAE parameters. Results indicated that ethanol concentration and extraction temperature were the most and least significant factors in achieving maximum recoveries of the yields, respectively. The selection of factor levels for optimization process was obtained based on the pre-evaluation of factors (OFAT). The best points for optimizing the factors were extraction time (2-4 min), microwave power (500-700 W and 400-600 W), ethanol concentration (40-80% and 20-60%), feed-to-solvent ratio (1:8-1:12 and 1:18-1:22 g/mL) and constant temperature of 70 °C, respectively. The optimal MAE conditions for fenugreek seed and Aloe vera leaves extraction yield, TSC and TPC were at 2.84 min, 572.50 W, 63.68%, and 1:9 g/mL. Based on the optimum condition, the responses of extraction yield, TSC and TPC of fenugreek seed were 26.04 ± 0.88%, 195.89 ± 1.07 mg DE/g d.w., 81.85 ± 0.61 mg GAE/g d.w, and for Aloe vera leaves extracts in MAE were 2.79 min, 478.95 W, 43.38% ethanol, and 1:19 g/mL. Where, based on these conditions, the extraction yield, TSC and TPC of Aloe vera leaves extract were 36.17 ± 1.13%, 65.89 ± 0.77 mg OAE/g d.w and 73. 05 ± 1.05 mg GAE/g d.w, respectively. The extracts obtained via MAE and SE were also tested for its antioxidant capacity via 2,2-diphenyl-1-picrylhydrazyl (DPPH) and 2,20-azino- bis (3-ethylbenzothiazoline-6-sulfonic acid) (ABTS), structure and bonding using Fourier transform infrared (FTIR) and morphological studies using SEM. Results indicated that extracts obtained via MAE showed higher antioxidant capacity with low IC50 values of (195.27 ± 0.56 μg/mL; DPPH), (157.92 ± 1.11 μg/mL; ABTS), 12 identified peaks in FTIR for fenugreek seed and (275 ± 1.45 μg/mL; DPPH) (215.58 ± 0.57 μg/mL; ABTS), 11 peaks in FTIR and more wrapped and opened texture via scanning electron microscope (SEM), respectively. However, in SE it was (224.47 ± 0.77 μg/mL; DPPH), (199.67 ± 0.96 μg/mL; ABTS) for fenugreek seed and (305.79 ± 0.66 μg/mL; DPPH), (263.29 ± 1.21 μg/mL; ABTS), with 6 identified peaks via FTIR and closed pores showed via SEM in both plants, respectively. kinetic studies and dielectric properties for MAE were also carried out. The LC-QTOF-MS result of optimized extracts also confirmed the presence of 58 saponins and 27 phenolic compounds in fenugreek seed and 29 saponin with 32 phenolic compounds in Aloe extract. The optimized extracts also indicated surfactant properties such as wetting, reduction of water surface tension, foaming and emulsification properties. Thus, these extracts can be a promising source of saponins, phenolics, antioxidants and natural co-emulsifier for food, cosmetics and pharmaceutical products.